Incidence and Risk Factors for Thoracic Spine Pain in the Working Population: The French Pays de la Loire Study. Issue 11 (November 2014) - Roquelaure, Yves; Bodin, Julie; Ha, Catherine; Le Marec, Fabien; Fouquet, Natacha; Ramond‐Roquin, Aline; Goldberg, Marcel; Descatha, Alexis; Petit, Audrey; Imbernon, Ellen
<x xml:space="preserve">Abstract</x> Objective To examine the incidence and risk factors for incident thoracic spine pain (TSP) in workers representative of a French region's working population. Methods In this prospective study, 3, 710 workers were assessed in 2002–2005, and 2, 332 (62.9%) of them were reassessed in 2007–2010. TSP was assessed by a self‐administered Nordic questionnaire at baseline and at followup. At baseline, all participants completed a self‐administered questionnaire on personal factors and work exposure. A total of 1, 886 subjects (1, 124 men and 762 women) without TSP at baseline were eligible for analysis. Associations between incident TSP and risk factors at baseline were analyzed by multivariate logistic regression. Results The incidence rate of TSP was 5.2 (95% confidence interval [95% CI] 3.9–6.6) per 100 men and 10.0 (95% CI 7.8–12.1) per 100 women. TSP was often associated with low back pain and neck pain. TSP in men was associated with age (odds ratios [ORs] ranging from 2.6 [95% CI 0.95–7.1] at 30–39 years to 6.0 [95% CI 2.1–17.3] at ≥50 years), being tall (OR 2.2 [95% CI 1.2–3.9]), frequent/sustained trunk bending (OR 3.0 [95% CI 1.5–6.1]), lack of recovery period or change in the task (OR 2.0 [95% CI 1.2–3.6]), and driving vehicles (OR 2.8 [95% CI 1.4–5.5]). Being overweight or obese was associated with lower risk (OR 0.5 [95% CI 0.3–0.96]). TSP in women was associated with high perceived physical workload (OR 1.9 [95% CI 1.1–3.3]), after adjustment for confounding variables. Conclusion The risk model of TSP combined personal and work‐related organizational and physical factors. Trunk bending appeared to be a strong independent predictor of TSP in this working population.